Identifikasi Karakteristik Covid-19 Terhadap Persepsi Jumlah Kasus Positif, Sembuh dan Kematian Akibat Covid-19 di Indonesia - Iko Sarikanti Ponangsera; Rio Khoirudin Apriyadi; Dedy Hartono; Wilopo Wilopo (University of Bengkulu, 2021)
[Identification of the Characteristics of Covid-19 Against Perceptions of the Number of Positive Cases, Cures and Deaths Due to Covid-19 in Indonesia] This research is a quantitative descriptive study with data exploration as the blade of analysis. The quantitative descriptive approach in question is an attempt to describe the characteristics of Covid-19 by exploring the perception of the number of positive cases, recovered and died due to Covid-19. The data in this study are secondary data collected through official reports from various stakeholders such as the Indonesian Ministry of Health, the Covid-19 Handling Task Force, and Kawalcovid19. The results of the study illustrate that based on gender, men have a higher risk of Covid-19 with 461,360 positive cases (50.50%) and 14,703 deaths (56.30%) and women have the characteristics of cured cases. more than men with 372,423 people (50.20%). Based on age, in the period 15 March 2020 to 22 January 2021 positive cases of Covid-19 in Indonesia were dominated by people of productive age, between 31-45 years with 280,139 people, (30.80%), 19-30 years with 230,812 people (25.30%). Healed cases were dominated by the age of 31-45 years with 212,198 people (22.60%). Meanwhile, the number of cases of death due to Covid-19 was dominated by ages ?60 years, totaling 12,078 people (45%) with an increasing mortality rate based on age. By province, the highest positive cases of Covid-19 were in DKI Jakarta Province with 266,404 people (24.98%) and the lowest was in North Maluku Province with 3364 people (0.31%), and the highest cases of recovered Covid-19 were in DKI Jakarta Province. 238,546 people (27.66%) and the lowest was in West Sulawesi 1992 people (0.23%), and the highest cases of death due to Covid-19 were in East Java Province 7733 people (26.10%) and the lowest was in West Kalimantan 30 people (0.10%).